The Clinical Efficacy and Safety of Enhanced Recovery After Surgery for Cesarean Section: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Observational Studies - Meng, Xianhua; Chen, Kai; Yang, Chenchen; Li, Hui; Wang, Xiaohong (Frontiers in Medicine, 2021)
Background Enhanced recovery after surgery (ERAS) protocols have been adopted in some maternity units and studied extensively in cesarean section (CS) in the last years, showing encouraging results in clinic practice. However, the present evidence assessing the effectiveness of ERAS for CS remains weak, and there remains paucity in the published literature, especially in improving maternal outcomes. The aim of our study was to systematically evaluate the clinical efficacy and safety of ERAS protocols for CS. Methods A systematic literature search of PubMed, Embase, and the Cochrane Library was performed up to October 2020. All randomized controlled trials (RCTs) and observational studies that applied ERAS for patients undergoing CS were considered for inclusion in this study, comparing effect of ERAS protocols with conventional care on length of hospital stay (LOS), postoperative complications, readmission rate, postoperative pain score, postoperative opioid use, and cost of hospitalization. All statistical analyses were conducted using the Revman5.3 software. Results Ten studies (Four RCTs and six observational studies) involving 16,391patients were included. ERAS was associated with a significant reduction in LOS (WMD − 7.47 hours, 95%CI: −8.36 to − 6.59, P<0.00001), and lower incidence of postoperative complications (RR: 0.50, 95% CI: 0.37 to 0.68, P<0.00001).Moreover, pooled analysis suggested that postoperative pain score (WMD: –1.23, 95% CI: –1.32 to –1.15, P<0.00001), opioid use (SMD:-0.46, 95% CI -0.58 to -0.34, P<0.00001) and hospital cost (SMD:-0.54,95% CI -0.63 to -0.45, P<0.00001) were significantly lower in ERAS group than in conventional care group. No significant difference was found with regard to readmission rate (RR: 0.86, 95% CI: 0.48 to1.54, P=0.62). Conclusions The available evidence suggested that ERAS applying to CS significantly reduced postoperative complications, lowered postoperative pain score and opioid use, shortened the hospital stay and potentially reduced hospital cost without compromising readmission rates. Therefore, ERAS protocols implementing in CS appears to be safe and effective. However, the conclusions should be caution owing to the limited number and methodological quality of included studies; hence, future large, well designed and conducted studies, with better methodological and reporting quality are needed to enhance the body of evidence.